How the New International recommendation for Electrocardiographic interpretation in Athletes would change our practice - Roberto Ferrara; Andrea Serdoz; Mariangela Peruzzi; Elena Cavarretta (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Recent evidences in the prevention of sudden cardiac death (SCD) confi rmed the importance of pre-participation cardiovascular screening in athletes to early identify, and further disqualify from the competition, all the athletes, if any, affected by life-threatening serious cardiac pathologies that can lead to SCD [1-2]. At present, there is no consensus regarding the optimal strategy for athletes' pre-participation screening. However, previous data showed that adding the ECG to pre-participation screening evaluation increased the accuracy to detect an underlying cardiovascular disease, in comparison with physical examination and medical history alone [3-4]. In the past, different criteria have been proposed, so a team of experts in sports cardiology aimed to standardize the criteria in ECG interpretation, in order to achieve the maximum sensibility and to improve the specifi city, because of the number of false positive is strictly related with the type of criteria and the experience of the operators.